Influence of Use of Different Media on Political Attitude and Political Participation - Kaur, Manpreet; Verma, Rajesh (Indian Journal of Marketing, 2022)
Information dissemination is not limited to conventional media as the advent of new media has transformed the entire political scenario. In a democratic country like India, people prefer to have information from different media like print media, broadcasting media, outdoor media, and new media, etc., which may impact their political attitude and participation. Therefore, the focus was to study the relative influence of different media on political attitude and political participation. A cross-sectional descriptive research design having a sample of 497 eligible voters was used. OLS regression analysis was used, and it was observed that media use for political information was a significant influencer for political participation, followed by political attitude, political knowledge, interest, and efficacy. Among all, social media was found to have a relatively higher significant positive influence, but traditional media cannot be ignored. The study results will contribute to the conceptualization of media behavior while considering multiple media for political information.